2014
DOI: 10.1093/humrep/deu292
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic endometritis in repeated unexplained implantation failure and the IVF success rate after antibiotic therapy

Abstract: A prospective randomized clinical trial is needed to confirm our findings but in women with RIF a hysteroscopic evaluation of the uterine cavity to exclude CE should be considered and appropriate antibiotic treatment should be given before submitting the patient to a further IVF attempt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
422
4
26

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(478 citation statements)
references
References 32 publications
26
422
4
26
Order By: Relevance
“…The authors observed that the expression of prolactin and insulin-like growth factor binding protein-1, markers of decidualization, and of steroid hormones receptors were altered in endometrial samples from CE patients. These results may explain the effects of CE on implantation and maintenance of pregnancy previously reported in ART cycles [28,29].…”
Section: Prp and Human Reproductionsupporting
confidence: 68%
See 1 more Smart Citation
“…The authors observed that the expression of prolactin and insulin-like growth factor binding protein-1, markers of decidualization, and of steroid hormones receptors were altered in endometrial samples from CE patients. These results may explain the effects of CE on implantation and maintenance of pregnancy previously reported in ART cycles [28,29].…”
Section: Prp and Human Reproductionsupporting
confidence: 68%
“…Generally, endometritis is asymptomatic or only accompanied by mild disturbances. Even histological analysis of endometrial biopsies may miss the diagnosis, as the identification of leukocytes in the endometrial stroma is a normal finding, particularly before menstruation [27,28]. In ART, the presence of endometritis is associated with overall lower success rates and 30.3% of the patients with repeated implantation failure are diagnosed with CE [28,29].…”
Section: Prp and Human Reproductionmentioning
confidence: 99%
“…Ceci peut s'expliquer par l'impact positif d'une possible brè che endomé triale consé cutive au passage de l'hysté roscope. [24]. Enfin, l'analyse des caryotypes des couples prescrits au dé cours du bilan d'é chec d'implantation retrouvait 2 anomalies à considé rer comme « pathologiques », c'est-à -dire pouvant avoir un impact sur la fonction de reproduction, chez les femmes seulement.…”
Section: Discussionunclassified
“…В последние годы для морфофункциональной диагностической оценки эндометрия широко используется офисная гистероскопия. Этот ме-тод является высокоспецифичным и чувстви-тельным (40-80 %) при диагностике полипов и хронического эндометрита [3][4][5] ■ Complex clinic-morphological study of uterine cavity scraping and a comparative hysteroscopic study of 964 women with infertility and unsuccessful IVF attemps were carried out. For the first time two prognostically meaningful clinicmorphological forms of chronic endometritis-polypoid and lymphofollicular are described.…”
unclassified